Optimizing Village Administration and Public Information Access through the Implementation of an Electronic Archive System in Desa Marga Mukti - Arifin, Ahmad (YHMM PUBLISHING, 2025)
The development of digital technology has transformed administrative processes by providing faster, more efficient, and accessible solutions. In village governance, managing official correspondence remains a critical activity that often faces challenges in organization, accessibility, and transparency. This study presents the design and implementation of an electronic archive (e-archive) system for Desa Marga Mukti, Penarik District, Mukomuko Regency, using a mobile web-based platform. The system was developed with the Waterfall method, ensuring a structured and sequential approach to software development. The e-archive facilitates the management of incoming and outgoing correspondence, improves administrative efficiency, and supports public information disclosure. The system is user-friendly, easily accessible to village officials, and contributes to better governance by streamlining administrative tasks and promoting transparency in Desa Marga Mukti